Aplikasi Sejarah Masuknya Islam Di Bengkulu Berbasis Android Menggunakan Algoritma Linear Congruent Method - Rivaq Afthal; Dwita Deslianti (Jurnal Media Infotama, 2022)
The entry of Islam to Bengkulu is inseparable from the development of Islam in Indonesia since the 13th century which was initiated from the 8th century. In addition to political and trade routes, the process of the entry of Islam into Bengkulu was also influenced by marriages and da'wah from local religious figures. Not many people know the history of the entry of Islam to Bengkulu because of the lack of media that tells about it. Many journals discuss the process of the entry of Islam to Bengkulu. To help children or teenagers in knowing the history of Islam in Bengkulu, they need media that can interest them and one of them is by building an Android application for the history of Islam in Bengkulu. By using this application, it will be possible to increase the user's interest in knowing the history of the entry of Islam to Bengkulu and its development so that it can add historical insight. In addition, the application will display Islamic religious figures or Ulama who have contributed at that time. The application also provides a question and answer facility as a form of interaction with the user. The question and answer process requires a randomization method so that the questions that appear are not monotonous. To get random numbers that constantly randomize the problem requires a special algorithm. One of the algorithms used is the Linear Congruential Generator or if it is converted into Indonesian it becomes a Random Number Generator. Application History of the Entry of Islam in Bengkulu Based on Android Using the Linear Congruent Method Algorithm was successfully built using android studio 4.1 software. 1. The application is built using the java programming language as the coding process and xml as the coding to build the appearance (User Interface). The application can provide readings about the process of entering Islam in Bengkulu, the relics of the past Islam and the indicted Ulama in Bengkulu. The application provides questions and answer choices as an exercise process and displays the results. The linear congruential method algorithm can randomize the questions to be displayed.